Analysis of Availability of Human Resources and Infrastructure Facilities in Supporting the Successful Learning - M Rofiq ‘Asmawi; Abd Kholid (SCHOOLAR: Social and Literature Study in Education, 2023)
The purpose of this study was to determine the factors that caused the Hamalatul Quran Islamic Boarding School Jogoroto Jombang to be able to educate its students in the process of memorizing the Koran quickly. The subjects in this study were Santri Pondok Pesantren Hamalatul Quran Jogorto Jombang, data collection used in the form of observation, interviews, documentation. The type of data analyzed produces qualitative data. The results of this study are: 1) the feasibility of human resources and infrastructure in supporting the successful learning of male students at the Hamaltul Quran Islamic Boarding School Jogorto Jombang. 2) the effectiveness of human resources and infrastructure in supporting the successful learning of male students at the Hamalatul Quran Islamic boarding school Jogorto Jombang.